Umbilical Cord Blood Mononuclear Cell Treatment for Neonatal Rats With Hypoxic Ischemia - Lyu, Hao; Sun, Dong Ming; Ng, Chi Ping; Cheng, Wendy S.; Chen, Jun Fan; He, Yu Zhong; Lam, Sin Yu; Zheng, Zhi Yuan; Huang, Guo Dong; Wang, Chi Chiu; Young, Wise; Poon, Wai Sang (Frontiers in Cellular Neuroscience, 2022)
Background Hypoxic-ischemic encephalopathy (HIE) occurs when an infant’s brain has not received adequate oxygen and blood supply, resulting in ischemic and hypoxic damage. Currently, supportive care and hypothermia therapy have been the standard treatment for HIE. However, there are still over 20% of treated infants died and 19–30% survived with significant disability. HIE animal model was first established by Rice et al., involving the ligation of one common carotid artery followed by hypoxia. In this study, we investigated human umbilical cord blood (HUCB) and its two components mononuclear cell (MNC) and red cell fraction (RCF) in both short and long term study using a modified HIE rat model. Methods In this modified HIE model, both common carotid arteries were occluded, breathing 8% oxygen in a hypoxic chamber for 60-min, followed by the release of the common carotid arteries ligature, mimicking reperfusion injury. For cell therapeutic study, cells were intravenously injected to HIE rat pups, and both behavioral and histological changes were assessed at selected time points. Result Statistically significant behavioral improvements were demonstrated on Day 7 and 1 month between saline treated HIE rats and UCB/MNC treated rats. However, at 3 months, the therapeutic improvements were only showed between saline treated HIE animals and MNC treated HIE rats. For histological analysis 1 month after cell injection, the number of functional neurons were statistically increased between saline treated HIE and UCB/MNC/RCF treated HIE rats. At 3 months, the significant increase in functional neurons was only present in MNC treated HIE rats. Conclusion We have used a bilateral temporary occlusion of 60 min, a moderately brain damaged model, for cell therapeutic studies. HUCB mononuclear cell (MNC) therapy showed benefits in neonatal HIE rats in both short and long term behavioral and histological assessments.